PELATIHAN ENGLISH DEBATE PARLIAMENTARY SYSTEM BAGI GURU MGMP BAHASA INGGRIS SMK SE-KOTA BATAM - Maldin, Siska Amelia; Silitonga, Frangky; Wibowo, Agung Edy (JURNAL KEKER WISATA, 2024)
Community service is one of the mandatory duties of lecturers as part of the realization of the Tri Dharma of Higher Education activities. In line with this, Tri Dharma activities are focused on important activities in contributing to improving the quality of life of the community, especially in developing skills that can be used in a wider range of society. One of the activities carried out was English Debate Parliamentary System Training for Vocational High School English MGMP Teachers throughout Batam City at the Batam Tourism Polytechnic. This training aims to provide information to Gugus Cahaya Jingga PAUD teachers regarding the English Debate Parliamentary System. The specific target to be achieved is to make GUGUS CAHAYA JINGGA PAUD teachers skilled in implementing the English Parliamentary Debate System in learning.